Election Voting and Public Library Use in the United States - Lund, Brady D.; Hendrickson, Beth L.; Walston, Matthew (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2020)
Objective - This study examines whether a correlation exists between state-wide voting in federal elections and state average per capita visits to public libraries in the U.S. In so doing, it provides insight into the extent to which library patronage is affiliated with political leaning.Methods - An analysis of data from the 2010, 2012, 2014, and 2016 Public Libraries Survey and election results from the 2010, 2012, 2014, and 2016 Presidential and House of Representatives elections (by state) is performed with the assistance of Tableau, a data visualization program. Scatter plots provide a visual representation of the data, while correlation coefficients indicate the strength of relationship between voting and library visits per capita.Results - The findings reveal no significant relationship between public library use and the vote share of a political party in elections among a state's population.Conclusions - The political leaning of a state appears to have no correlation with the frequency of library usage among that state’s population.